Inflammation and immune response in the development of periodontal disease: a narrative review - López-Valverde, Nansi; Quispe-López, Norberto; Blanco Rueda, José Antonio (Frontiers in Cellular and Infection Microbiology, 2024)
We present this critical review with the aim of highlighting the current status of periodontal diseases, focusing on the relevance of host modulating agents and immune pathways, in addition to new complementary therapeutic approaches for the treatment of these pathologies. Periodontal diseases are prevalent pathologies worldwide and the main cause of edentulism in the adult population. Their pathogenesis seems to be based on a dysbiosis of the oral microbiota that interacts with the host’s immune defenses and is responsible for the inflammatory/immune response, which would be modified by a number of conditions such as individual susceptibility, environmental and sociodemographic factors, certain systemic pathologies and the individual’s genetic condition, among others. Numerous studies have reported on the complex web of inflammatory mediators in periodontal disease and their role in tissue destruction as well as in homeostatic imbalance. Precisely, the role of epigenetics as a modifier of the host genetic condition has captured research attention in recent years. Therefore, this mini-review first discusses an updated etiological hypothesis of periodontal disease and the roles of certain cytokines in the immune response. In addition, the latest therapeutic trends with new developments and future perspectives are summarized.